Assessing Murphy Sequence as a Clinical Element in Acute Appendicitis Diagnosis - Andy Rocha Quintana; Orisel Fernández Suárez; Elianne Rodríguez Larraburu; César Jorge Castro Rodríguez (Medisur)
Background: at present, the presence or lack of agreement between clinical diagnosis and evidence when exploring the abdominal cavity and performing excision of the pathological piece in cases of acute appendicitis, has become an increasingly contested issue. Objective: to characterize the presentation of Murphy Sequence in patients who underwent acute appendicitis surgery. Methods: descriptive study on a case series of patients who underwent acute appendicitis surgery in the General University Hospital of Cienfuegos between March and September 2006. Variables analyzed: age, sex, skin color, evolution duration and order of appearance of symptoms, presentation of Murphy Sequence, complementary tests and pathological diagnosis. Results: the average age for cases where Murphy Sequence was not presented was 34 years old, predominantly brown skinned males. The sequence was not completed in 96, 8% of cases, mainly those found in catarrhal stage. Laparoscopy was not performed in 69.7% of patients and, within this group, 97.7% of patients did not complete the sequence. In 51.9% of the cases, the first symptom was epigastric pain that then moved to the right iliac fossa. A broad spectrum of values of white blood cells was found in cases of catarrhal appendicitis. Conclusions: in 96.8% of cases Murphy Sequence was absent. Even in cases of long evolutions, these symptoms were not related to the disease stages.